Some Physicochemical Characteristics of Zeolite-bearing Deposits In the West and South of the Coastal Chain - مصطفى حبيب; عقل رومية; نسرين سفلو (Latakia University Journal -Basic Sciences Series, 2022)
Natural zeolite is one of the important materials that began to be used in industry and agriculture in the sixties of the last century, due to its unique properties. The adsorption of methylene blue was studied for three samples of crude deposits containing zeolite within the study area (M, R, J). The specific surface area of ​​these deposits was determined, and analyzed by (DTA-TG), where the results showed that the adsorption curve for methylene blue is of a type the langmoire and belongs to the class L according to the classification of Gillis and his colleagues. The research concluded that the adsorption capacity of the monolayer Xm for the first sample was Xm for the second sample Xm , while for the third sample it was Xm . The receptive surface area of ​​methylene blue particles is in the first sample SMB=81.63 m2/g, and in the second sample SMB=51.29 m2/g, in the third sample SMB=73.68 m2/g. The differential thermal analysis (DTA-TG) showed that the three samples have thermal stability within a wide range and that there is a slight and othermic effect at the degree ( ) caused by slight thermal in sintering the zeolitic structure. In general, the study showed that the studied deposits are suitable for their acceptable surface areas as a good adsorbent material.